Impact of Tai-Chi on falls among preclinically disabled older people: A randomized controlled trial - Day, L.; Hill, Keith; Stathakis, V.; Flicker, L.; Segal, L.; Cicuttini, F.; Jolley, D. (Elsevier Inc., 2015)
Objective: To investigate the effectiveness of tai-chi in preventing falls among community-dwelling older people. Design: Multisite parallel group individually randomized controlled trial. Setting: Melbourne, Australia. Participants: Preclinically disabled community-dwelling people 70+years (n=503), without major medical conditions or moderate to severe cognitive impairment. Intervention: Sixty-minute modified Sun style tai-chi group-based exercise program twice weekly for 48weeks; control intervention was a seated group-based flexibility exercise program of the same dose. Measurements: All falls, self-reported using a monthly calendar, analyzed at 24weeks and 48weeks. Injurious falls reported in follow-up telephone interviews for each reported fall. Results: The adjusted fall incidence rate ratios at 24 and 48weeks were 1.08 [(95% confidence interval (CI) 0.64-1.81)], and 1.12 (95% CI 0.75-1.67), respectively. A higher proportion of intervention participants ceased attendance in the first 24weeks (difference 17.9%, 95% CI 9.6-25.8), and the second 24weeks (2.7%, 95% CI-5.0 to 10.4). Intervention participants who ceased attendance had lower left quadriceps strength (difference 3.3kg 95% CI 0.15-6.36) and required longer to complete the timed up and go test (difference 1.7seconds 95% CI 0.22-3.17) at baseline. Conclusions: This study does not support modified Sun style tai-chi as a falls prevention measure among relatively well community-dwelling older people with modified mobility and at increased risk of disability. Insufficient intervention intensity, or low exercise class attendance may have contributed to the lack of effect, as may have attrition bias among the intervention group.